HUNGARIAN GIBRALTAR AND SERBIAN ATHENS - Pálfalvi, Lajos (Porównania, 2012)
The author ponders over the identity of the Hungarian authors who after the year 1920 became citizens of other countries and members and co-creators of not only their own national culture but also the culture of other countries, such as Romania, Czechoslovakia and Yugoslavia, which took over the former Hungarian territories. According to him, the borders of the Hungarian country do not have much in common with the borders of the Hungarian culture. The article focuses more in depth at the situation of the writer who works in Yugoslavia, in the region of Vojvodina. Attila Balázs’ work relativises the categories of centre and province, North and South, determined in the native culture. Balázs, who became an emigrant against his own will, describes the role of Budapest and the Hungarian provinces, the “floating away” of the Hungarian city of Újvidék which all of a sudden was found within the borders of Yugoslavia towards the Balkan culture and the appearing of new cultural circles that revised the traditional opposition between North and South. The city of Újvidék/Novi Sad becomes a fully multicultural phenomenon and is awarded the function of a Hungarian Gibraltar while simultaneously becoming a buzzing centre of culture.